FACTORS AFFECTING EARNINGS QUALITY: THE MODERATING ROLE OF MANAGERIAL OWNERSHIP - Dani, Andrian; Kholilah, Kholilah (Kesatuan Press, 2025)
This study examines the impact of capital structure, profitability, Corporate Social Responsibility (CSR), and accounting conservatism on earnings quality, with managerial ownership as a moderating factor. Earnings manipulation has been carried out by directors and deputy directors of the Renault-Nissan-Mitsubishi Alliance of approximately US44 million, affecting the quality of earnings generated. Focusing on industrial and energy sector companies listed on the IDX from 2021 to 2023, this study uses a quantitative approach, selecting samples using purposive sampling techniques and analyzing 39 selected companies using panel data regression and MRA in E-Views. The results show that profitability and CSR negatively affect earnings quality, while capital structure and accounting conservatism have no significant impact. Managerial ownership moderates the effects of capital structure, profitability, and CSR on earnings quality but does not influence the role of accounting conservatism. The results of this study suggest that companies in the industrial and energy sectors should optimally implement CSR and accounting conservatism to attract investors, improve earnings quality, and support management and stakeholder decision-making.